Creating Educational Math Games Using Construct 2 Software - Farhan Zaky; Ricky Zulfiandy; Achmad Fikri Sallaby (Jurnal Media Computer Science, 2026)
This study aims to develop a mathematics educational game for seventh-grade junior high school students using Construct 2 software, focusing on algebra and plane geometry. The research method used is experimental, covering needs analysis, system design, implementation, and black box testing. The game is designed with interactive features such as multiple-choice quizzes, visual simulations, and score tracking to enhance motivation and conceptual understanding. A questionnaire completed by 15 respondents showed that 86.7% agreed/strongly agreed the game interface was easy to use, 80% felt the game supported concept comprehension, and 93.3% would recommend the game. Functional testing confirmed that all features (navigation, content, quizzes, and score storage) operated optimally. The game aligns with the Merdeka Curriculum, which emphasizes competency-based and contextual learning. The results conclude that the Construct 2-based educational game is effective as an interactive learning tool, increases student engagement, and is suitable for further development by adding collaborative features and expanding its content.